Economic interpretation of history - Lill, Percy E. (My University, 1907)
Introduction: The careful student of history cannot fail to notice the tendency, quite common among historians, to overestimate the influence of great men in shaping the destinies of nations. They make the story of national life to appear as a composite biography of those who played leading roles in the drama of politics or the tragedy of war. Individuals are made masters of human destiny instead of creatures of opportunity. While the "Great men" theory, and the theory of "Moral forces" in historic interpretation are by no means to be undervalued, the contention is here made, that their importance, as historic factors, has been greatly exaggerated. A casual reader of history will find nothing whatever, in much of it, to give any clue to the reasons or causes of the changes which are chronicled. The historian who narrates the deeds of an Alexander or a Napoleon, is prone to forget the people and conditions which made their careers possible. We rarely read of the years of suffering and misery which these people underwent as a result of their country's having been drained of its resources. History tells of the fall of Napoleon, but it tells only, that his army was defeated, while he, himself, was captured and imprisoned. It does not mention the exhaustion of resources which the country suffered at the time and which made it impossible to raise men and supplies. Nor does it tell of the economic principles which he antagonized when he issued the famous Berlin and Milan decrees, that were so instrumental in alienating the people and capital of the nation from his support. This constitutes the real fall of Napoleon. Before entering into the discussion of this subject, it may be well to…
Citation: Lill, Percy E. Economic interpretation of history. Senior thesis, Kansas State Agricultural College, 1907.
Morse Department of Special Collections
Keywords: World History; Economics in History; Theory of World History; Perspective on World History; Theses